Sanad Authority in a Weberian Analysis of ‘Ālīy and Nāzil Transmission in al-Azkār of an-Nawawī - Hartati, Hartati; Iskandar, Amin; Febriyanto, Alfian; Kusnandar, Engkus; Nugraha, Andi; Rahmayanti, Mia; Taeri, Shayan (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
This paper discusses the sociology of Max Weber's Interpretive in the sanad 'Ālīy and Nāzil of the hadiths contained in the book Al-Ażkār by Imām an-Nawāwῑ. This study employs a literature review approach by analyzing relevant primary and secondary sources. The findings indicate that Max Weber’s sociology of Interpretive encompasses four key dimensions: types of social action, value and goal rationality, verstehen, and authority. This type of social action appears when Imām an-Nawāwῑ only lists the names of companions in the hadith sanad. The rationality of the value and approach of Weber's verstehen can be seen in the hadith sanad, which is summarized for the purpose of understanding and beliefs of the reader. The results of takhrij show that the first hadith narrated by Muslims has a sahih sanad and matan that corroborates QS. Al-An'ām (6:160). The second hadith narrated by at-Tirmidhi has sanad and matan daif. The third hadith narrated by Abu Daud is authentic and its matin corroborates QS. Al-Jumu'ah (62:9). The fourth hadith narrated by Abu Daud is sanad and his matan is daif, while the fifth hadith narrated by Abu Daud has sanad hasan sahih and matan that corroborates QS. Al-Ahzāb (33:56). The five hadiths show that Imām an-Nawāwῑ has a strong rationalization of religious interpretation. He understood the quality of the rawi through jarh wa ta'dil, so it is clear that religious interpretation is not only derived from revelation, but is also shaped by the structure and social dynamics of society.